Co-Creation Beyond Humans: The Arts of Multispecies Placemaking - Sachs Olsen, Cecilie (2022)
Placemaking, as a form of urban development often focusing on arts- and community-based approaches, is becoming a key site for responding to pressing social and environmental concerns around the development of sustainable urban futures. This article explores the potential of arts-based methods to develop a “multispecies placemaking” in which “the community” is expanded to also include non-human species. Drawing on a performative event aiming to put the idea of multispecies placemaking into practice, the article brings together theories and practices of the evolving field of multispecies art with the more established field of socially engaged art to discuss challenges of co-creation and participation from a multispecies perspective. It concludes with a reflection on the possibilities of arts-based methods to foster not only methodological innovation within the field of placemaking but also to suggest a re-thinking of what placemaking is and could be.